1997
DOI: 10.1111/j.1467-9280.1997.tb00690.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Language Learning: Listening (and Learning) Out of the Corner of Your Ear

Abstract: Two experiments investigated the performance of first-grade children and adults on an incidental language-learning task. Learning entailed word segmentation from continuous speech, an initial and crucial component of language acquisition. Subjects were briefly exposed to an unsegmented artificial language, presented auditorily, in which the only cues to word boundaries were the transitional probabilities between syllables. Subjects were not told that they were listening to a language, or even to listen at all;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

35
468
7
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 501 publications
(534 citation statements)
references
References 25 publications
35
468
7
5
Order By: Relevance
“…It is in line with previous results showing that statistically driven segmentation can occur even in conditions in which attention is not fully allocated to the AL stream (e.g., Toro et al, 2005; see also Saffran, Newport, Aslin, Tunick, & Barrueco, 1997, who observed ALL with a concurrent drawing task), and with listeners who cannot be formally instructed to attend to the speech stream (human infants-see, e.g., Saffran, Aslin, & Newport, 1996-or nonhuman primates-see, e.g., Hauser, Newport, & Aslin, 2001). More generally, these results converge with evidence showing that the speech signal (or other dynamic and complex auditory stimuli; see, e.g., Jones, Macken, & Murray, 1993) is processed even when participants are asked to ignore it, as demonstrated, for example, by the irrelevant sound effect (or irrelevant speech effect, cf.…”
Section: Methodssupporting
confidence: 80%
See 1 more Smart Citation
“…It is in line with previous results showing that statistically driven segmentation can occur even in conditions in which attention is not fully allocated to the AL stream (e.g., Toro et al, 2005; see also Saffran, Newport, Aslin, Tunick, & Barrueco, 1997, who observed ALL with a concurrent drawing task), and with listeners who cannot be formally instructed to attend to the speech stream (human infants-see, e.g., Saffran, Aslin, & Newport, 1996-or nonhuman primates-see, e.g., Hauser, Newport, & Aslin, 2001). More generally, these results converge with evidence showing that the speech signal (or other dynamic and complex auditory stimuli; see, e.g., Jones, Macken, & Murray, 1993) is processed even when participants are asked to ignore it, as demonstrated, for example, by the irrelevant sound effect (or irrelevant speech effect, cf.…”
Section: Methodssupporting
confidence: 80%
“…In sum, ALL was penalized in a graded way by a depletion of attention resources, independently of the fact that Likewise, attention load and intention to learn may have different and perhaps additional effects on ALL. Their joint action may, for example, explain why in Saffran and colleagues' studies, ALL performance was much lower (only 59%) when participants performed a resource-consuming task in incidental learning (Saffran et al, 1997) than when there was no diverting task and learning was intentional (in which case performance reached 76%; .…”
Section: All Performancementioning
confidence: 99%
“…Following exposure, infants showed sensitivity to the difference between the three-syllable sequences and foil sequences made up of the same syllables recombined in a different order, demonstrating that they were able to use the statistics of the input stream to discover word boundaries in connected speech (Saffran et al 1996a). Subsequent studies indicated that older children and adults also have this ability, becoming capable of discriminating between nonsense words and foil sequences after relatively short periods of exposure to input (Saffran et al 1996b(Saffran et al , 1997. Although statistical learning was initially implicated in language acquisition, it is a domain-general mechanism, also operating across nonlinguistic stimuli.…”
mentioning
confidence: 99%
“…Statistical learning has been demonstrated both when stimuli are presented passively without any explicit task (e.g., Saffran et al 1999;Aslin 2001, 2002;Toro et al 2005), and when participants are engaged in a cover task unrelated to the underlying pattern (Saffran et al 1997, Turk-Browne et al 2005). In addition, statistical learning seems to be unaffected by the precise instructions given to participants (Arcuili et al 2014;Batterink et al 2015).…”
mentioning
confidence: 99%
“…Marsick and Watkins 2001;Newton 2013;Saffran et al 1997;Webb 2008), as we feel that it makes a clearer distinction between a teacher's intended learning objectives and outcomes (both are terms widely used in the classroom), and those outcomes and objectives that were, from the teacher's perspective, wholly unintended. The use of 'unintended', unlike 'incidental', places a greater emphasis on the fact that whilst learning might have taken place in a particular lesson it was, from the teacher's perspective, unintended.…”
Section: Introductionmentioning
confidence: 99%